78.4k views
0 votes
What is 14 + 5x = 3 ( -x + 3 ) - 11

User Zontragon
by
5.4k points

2 Answers

7 votes

14+5x=3(-x+3)-11

(5x + 14) - (3 • (3 - x) - 11) = 0

3.1 Pull out like factors

8x + 16 = 8 • (x + 2)

8 • (x + 2) = 0

4.1 Solve : 8 = 0

4.2 Solve : x+2 = 0

x = -2


User James Thurley
by
5.7k points
5 votes

Answer:

X = -2

Step-by-step explanation:

Expand equation:

14 + 5x - 14 = -3x - 2 - 14

Subtract 14 from both sides:

14 + 5x - 14 = -3x - 2 - 14

Simplify:

5x = -3x - 16

Add 3x to both sides:

5x + 3x = -3x - 16 + 3x

Divide both sides by 8:

8x / 8 = -16 / 8

Simplify:

X = -2


- I.A -

User Erik Pedersen
by
6.0k points